ARABIC LANGUAGE TRADITION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The Arab world at that time was experiencing the rapid development of the natural sciences and the humanities. The term language (especially Arabic) is given the most honorable place here. Even the rulers of the Khilafah themselves showed great interest in linguistic research (the initiative to create grammar in the Arab world is believed to belong to Khalifa Ali, 656-661).